Enhancing Assertiveness Through Traditional Turkish Folk Dance - Züleyha Avşar (International Journal of Asian Education, 2023)
The present study investigates the effects of assertiveness training programs through folk dances on high school students’ assertiveness levels. Pre-test post-test with control group design has been used to examine. Furthermore, a questionnaire including one open-ended question asked students to learn their opinion on training and its effects on themselves. Experiment and control group participants were administered the Rathus Assertiveness Inventory, and experiment group participants received a two–hour assertiveness training program through folk dances per week over eight weeks. The study sample included 203 students who were in first grade in the same school. Results revealed that students in the experiment group had significantly higher assertiveness levels than those in the control group (P<0.05), and experiment group students defined that this assertiveness training program positively affected them and increased their awareness about themselves.